Conventional and Online Gambling: Emerging Challenges for the Wonogiri Regional Police - Rastra Patria Adiarta; Hanuring Ayu Ardhani Putri; Nourma Dewi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The proliferation of conventional and online gambling in Indonesia has created new challenges for law enforcement agencies, particularly in relation to evolving criminal modus operandi, the use of electronic evidence, and the increasing sophistication of digital technologies. This study aims to identify the forms and characteristics of gambling offenses within the jurisdiction of the Wonogiri Regional Police, analyze the implementation of Articles 303 and 303 bis of the Indonesian Criminal Code in investigative and criminal inquiry practices, and examine the obstacles encountered by law enforcement officers in addressing these offenses. The study employed an empirical juridical method with a socio-legal approach, utilizing interviews, observations, and document analysis as data collection techniques. The findings reveal that gambling activities have shifted toward more complex digital forms, while law enforcement efforts have been implemented through both preventive and repressive measures in accordance with prevailing legal provisions. The principal challenges include difficulties in obtaining electronic evidence, limited digital forensic capabilities, and inadequate inter-agency coordination. Therefore, strengthening institutional capacity, modernizing technological infrastructure, and enhancing public participation are essential to achieving more effective and sustainable strategies for combating gambling-related crimes.